Mining Stress Distribution in Stope and Overlying Rock Fracture Characteristics and Its Disaster-Pregnant Mechanism of Coal Mine Earthquake - Pengfei Lyu; Kangbin Lu; Xuehua Chen (Shock and Vibration)
The corresponding engineering effects are inevitable and occurred when the coal mines working face mining. The main manifestations are distribution of mining stress and fracture of overlying rock seams. The mining effects play a controlling role in the occurrence of dynamic disasters such as disastrous coal mine earthquakes and rock bursts. In view of this, taking No. 1305 working face mining of Dongtan coal mine for background, the distribution and transfer characteristics of mining stress in working face and fracture characteristics of roof rock formation were studied by theoretical analysis, numerical simulation, and microseismic monitoring. The change mechanism of stress, strain, strain rate, and energy of rock mass in the process of coal mine earthquake gestation was expounded by the Burgers mechanical model. The results show that the microseismic hypocenters are mainly concentrated near the increasing pressure zone and the fractured zone. The hypocenter first gathered at the main roof, and then, it gradually developed upward and returns to the main roof after mining. The distribution of microseismic frequency and advanced support pressure is basically consistent. The microseismic energy peak value area with respect to the support pressure peak value area often presented a certain lag. The relationship of empirical formula is inferred as YE=ME+∆d. The overlaying rock caving zone and fractured zone with height of 37.8 m and 95 m, respectively, were revealed by microseismic monitoring. It is 8.4% larger than the numerical result. It shows that the prediction results of overlying rock fracture height based on the distribution of large energy hypocenter points is well applied in the field, and the operations are simple and intuitive.